Study of the Potential of Mangrove Areas to Support Ecotourism in Mangunharjo Village, Tugu District, Semarang - Tefarani, Rahmadyan; Hidayat, Jafron Wasiq; Muhammad, Fuad (Devotion : Journal of Research and Community Service, 2023)
Mangrove ecosystems are one of the potential ecosystems to be developed as ecotourism areas. This study was designed to analyze the suitability of mangrove areas as objects of attraction in ecotourism development in Mangunharjo Village, Tugu District, Semarang City. This study looked at 5 variables, namely mangrove type, mangrove density, biota association,  thickness, and tides. Sampling was carried out at 3 stations, 10 plots each. Density data collection is done by counting each individual on each species in a sampling quadrant of 10 x 10 m. Identification of mangroves is carried out by Wetlands. The identification results recorded 8 species of mangrove plants found at the research station. A. marina and R. mucronata species are most commonly found at each station. Biota found in mangrove areas is quite diverse. The tides in the Mangunharjo area are not too high, so it is an area that is classified as very suitable for ecotourism development. The suitability of the Mangunharjo coastal tourism area for the development of marine ecotourism areas for the three stations in the category is very suitable to match the IKW value of 68.42 - 96.05%.